2021
DOI: 10.2166/wst.2021.185
|View full text |Cite
|
Sign up to set email alerts
|

Improving aeration systems in saline water (part II): effect of different salts and diffuser type on oxygen transfer of fine-bubble aeration systems

Abstract: The objective of the present study is to investigate the different effects on the oxygen transfer of fine-bubble aeration systems in saline water. Compared to tap water, oxygen transfer increases due to the inhibition of bubble coalescence. In Part I of the present study, we investigated in lab-scale experiments the effect of design of diffuser membrane. The objective of Part II is the assessment of effects of different salts, diffuser type and diffuser density. We measured the concentration of various salts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Our previous studies showed that in SW, f S,max as well as the maximum k L a were higher with a small slit membrane design than one with large slits [1]. For disc diffusers, the k L a increases by 10% when using the small slit diffuser membrane design compared with diffusers with the large slit design [2]. However, the improved k L a is accompanied by an increased diffuser pressure drop (due to the smaller slits) and, therefore, by a higher energy requirement for air supply.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous studies showed that in SW, f S,max as well as the maximum k L a were higher with a small slit membrane design than one with large slits [1]. For disc diffusers, the k L a increases by 10% when using the small slit diffuser membrane design compared with diffusers with the large slit design [2]. However, the improved k L a is accompanied by an increased diffuser pressure drop (due to the smaller slits) and, therefore, by a higher energy requirement for air supply.…”
Section: Introductionmentioning
confidence: 95%
“…The normalised k-value (k N ; -) describes the slope of the linear increase in f S until c Salt /CCC Salt = 1.0 and f S reaches f S,max . Since only the diffuser membrane design and q A,Disc affects f S,max or bubble diameter, but not the salt type [2,[11][12][13], it is reasonable that solutions of different salts and salt mixtures with the same c Salt /CCC Salt ratio and aerated with the same diffuser would present similar f S values. Other studies already showed the advantages of using a dimensionless concentration as independent parameter for analyses of hydrodynamics and oxygen transfer with different salt solutions in bubble columns [13][14][15].…”
Section: Modified Design Approach For Considering Salt Effect On K L Amentioning
confidence: 99%
See 3 more Smart Citations